1993
DOI: 10.1095/biolreprod49.3.582
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Embryotrophic Activity of Exogenous Protein-Free Oviduct-Conditioned Medium Used in Culture of Cattle Embryos1

Abstract: Bovine zygotes, obtained after in vitro maturation and fertilization of oocytes from slaughtered cow ovaries, were cultured in droplets of nonconditioned or conditioned medium on bovine oviduct cell monolayers. The media tested were Medium 199 alone and Medium 199 supplemented with 10% fetal calf serum (FCS). Oviduct conditioning increased both early cleavage and development to blastocysts. Only the effect on early cleavage was mimicked by FCS. The blastocysts obtained in serum-free conditioned medium (SFCM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
4

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 28 publications
1
52
1
4
Order By: Relevance
“…In contrast, the benefits observed using MDBK cells were lost with Vero cells, suggesting either that some cell lines are unable to remove inhibitory factors from a poor medium such as B2 or that inhibiting factors are produced by certain cell lines. In addition, contrary to studies reporting the existence of a low molecular weight molecule which enhanced embryo development (Minami et al, 1992;Mermillod et al, 1993), no beneficial effect was consistently observed in any specific fraction tested in our work. This supports the idea that cells are responsive only to certain media and that feeder cells do not improve embryo development through specific factors secreted into the medium but only act by changing the base medium.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast, the benefits observed using MDBK cells were lost with Vero cells, suggesting either that some cell lines are unable to remove inhibitory factors from a poor medium such as B2 or that inhibiting factors are produced by certain cell lines. In addition, contrary to studies reporting the existence of a low molecular weight molecule which enhanced embryo development (Minami et al, 1992;Mermillod et al, 1993), no beneficial effect was consistently observed in any specific fraction tested in our work. This supports the idea that cells are responsive only to certain media and that feeder cells do not improve embryo development through specific factors secreted into the medium but only act by changing the base medium.…”
Section: Discussioncontrasting
confidence: 99%
“…In the light of this, several studies have argued that a number of different cell lines may produce such a factor(s) Ouhibi et al, 1990;Minami et al, 1992;Bongso et al, 1993;Mermillod et al, 1993). In this study only B2 medium conditioned by MDBK cells improved embryo development, but no blastocyst formation was observed in B2 alone.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Expanded day 8 blastocysts from each treatment groups were fixed and stained as per the method described (Mermillod et al, 1993). These expanded blastocysts were then transferred individually onto glass microscopic slides and after drying at room temperature, fixed with 70% ethanol for 24 h. The fixed blastocysts were stained with 10 mg/ml bisbenzamide (Hoechst 33342) and 2.3% sodium citrate.…”
Section: Thiyagarajan and Valivittanmentioning
confidence: 99%
“…Expanded day eight blastocysts from each treatment group were fixed and Vitamin A as antioxidant in ovine in vitro fertilisation stained as per the method described by Mermillod et al (1993). These expanded blastocysts were then individually transferred onto glass microscopic slides and dried at room temperature.…”
Section: Fertilisation Of Oocytes In Vitromentioning
confidence: 99%